2020
DOI: 10.1038/s41598-020-66508-6
|View full text |Cite
|
Sign up to set email alerts
|

The optimal time interval between the placement of self-expandable metallic stent and elective surgery in patients with obstructive colon cancer

Abstract: A bridge to surgery (BtS) after a colonic stent for obstructive colon cancer has not been accepted as a standard treatment strategy. Also, there is no consensus regarding the optimal time interval for BtS. We aimed to identify the optimal timing for BtS after stent placement to decrease the oncologic risk. We retrospectively collected data of 174 patients who underwent BTS after stent placement for stage II or III obstructive colon cancer from five hospitals. We divided the patients into three groups based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Some reports show that a shorter interval could induce severe postoperative complications such as anastomotic leakage, 13,37 and others note that a longer interval could lead to a higher risk of tumor recurrence 38 . A recent multicenter study ( N = 174) showed that perioperative short‐term outcomes are not affected by the interval, although a longer interval (>7 days) is an independent negative risk factor for long‐term outcomes 14 . As the ESGE guideline recommends a short interval of approximately 2 weeks, a reasonable strategy may be to perform elective surgery as soon as possible after stenting, to strike a fine balance between potential adverse events and long‐term oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some reports show that a shorter interval could induce severe postoperative complications such as anastomotic leakage, 13,37 and others note that a longer interval could lead to a higher risk of tumor recurrence 38 . A recent multicenter study ( N = 174) showed that perioperative short‐term outcomes are not affected by the interval, although a longer interval (>7 days) is an independent negative risk factor for long‐term outcomes 14 . As the ESGE guideline recommends a short interval of approximately 2 weeks, a reasonable strategy may be to perform elective surgery as soon as possible after stenting, to strike a fine balance between potential adverse events and long‐term oncologic outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is reasonable to recommend colonic stenting, both to avoid emergency surgery and to prevent postoperative complications in patients with CRC and obstruction. Accumulating evidence shows that greater experience with colonic stenting (≥40 procedures) and a shorter interval between stenting and surgery (≤15 days) are important factors for reducing postoperative complications and improving oncologic outcomes 12–14 . However, there are no studies that detail the predictors of postoperative complications in patients with CRC undergoing BTS.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, stent-related complications were most frequently observed in patients who underwent surgery after 17 d[ 63 ]. On the other hand, a multicenter retrospective study on the optimal timing of elective surgery after SEMS placement by Kye et al [ 62 ] supports the concept that early elective surgery within seven days after SEMS placement correlates with better oncological outcomes than elective surgery after seven days. Currently, the ESGE guidelines state only that the time interval for surgery after SEMS placement should balance stent-related adverse events and surgical outcomes[ 47 ].…”
Section: Optimal Interval Between Sems Placement and Elective Surgerymentioning
confidence: 97%
“…At present, prospective comparative data on how the different intervals affect the short- and long-term outcomes are not available. Two retrospective studies have reported conflicting results regarding resection timing after decompression for postoperative morbidity and oncologic outcomes[ 62 , 63 ]. A retrospective study using the Dutch nationwide cohort demonstrated that surgery within 5–10 d resulted in a longer hospital stay, a lower rate of laparoscopic resection, and a higher rate of stoma creation than surgery after 11 d[ 63 ].…”
Section: Optimal Interval Between Sems Placement and Elective Surgerymentioning
confidence: 99%